数量补语(SHÙLIÀNG BǓYǓ) COMPLEMENTS OF QUANTITY: THEIR IMPORTANCE AND PRACTICE IN CHINESE GRAMMAR (International journal of artificial intelligence, 2024)
We hope that the research materials proposed in the article can be used as a means of teaching Chinese as a foreign language and promoting the effective development of new information. The main purpose of this study is to describe the complement of quantity as one of the components of Chinese grammar.